2022
DOI: 10.3389/fmolb.2022.1003045
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNAs in ferroptosis

Abstract: Ferroptosis is a newly discovered type of programmed cell death, which is closely related to the imbalance of iron metabolism and oxidative stress. Ferroptosis has become an important research topic in the fields of cardiomyopathy, tumors, neuronal injury disorders, and ischemia perfusion disorders. As an important part of non-coding RNA, microRNAs regulate various metabolic pathways in the human body at the post-transcriptional level and play a crucial role in the occurrence and development of many diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…In 2012, the concept of ferroptosis was proposed by Stockwell, and is characterized by Fe 2+ dependence, lipid peroxidation, and depletion of REDOX systems. Ferroptosis is involved in various diseases, such as malignant tumors, neurodegeneration, and ischemia–reperfusion injury 57 . As a result, molecules and drugs targeting ferroptosis have become a hot topic of research and development 58 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the concept of ferroptosis was proposed by Stockwell, and is characterized by Fe 2+ dependence, lipid peroxidation, and depletion of REDOX systems. Ferroptosis is involved in various diseases, such as malignant tumors, neurodegeneration, and ischemia–reperfusion injury 57 . As a result, molecules and drugs targeting ferroptosis have become a hot topic of research and development 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has indicated that ferroptosis is associated with cancer initiation, progression, and suppression [ 45 ]. Furthermore, miRNAs can either promote or suppress tumors through regulating ferroptosis by interfering with iron metabolism, lipid peroxidation, and the system Xc - /GPX4 axis [ 46 , 47 ]. EVO can affect the expression of non-coding RNAs and their target genes in cancer cells, suggesting that EVO can mediate gene expression at the post-transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies focused on exploring the role of miRNAs in regulating ferroptosis [ 35 , 36 , 37 ]. Several miRNAs that modulate cardiomyopathy, neuronal injury, and cancer-associated ferroptosis are summarized [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies focused on exploring the role of miRNAs in regulating ferroptosis [ 35 , 36 , 37 ]. Several miRNAs that modulate cardiomyopathy, neuronal injury, and cancer-associated ferroptosis are summarized [ 35 ]. Ferroptosis-regulating miRNAs [ 36 , 37 ] and circular RNAs [ 36 ] occurring in several cancer cells are summarized [ 36 ].…”
Section: Introductionmentioning
confidence: 99%